2020
DOI: 10.3390/su122410229
|View full text |Cite
|
Sign up to set email alerts
|

Making Room for Volunteer Participation in Managing Public Affairs: A Russian Experience

Abstract: In 2018, the United Nations Volunteers organization recognized that the governmental support for volunteering is a superior public management practice, offering the much-needed fuel for the integration of volunteering in politics, law-making, and social planning at the government level. The present article analyzes the current situation of governmental support for volunteering at federal, regional, and local levels of public administration in the Russian Federation as a precondition for making coproduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Results showed that 50.1 % of civil servants in Chongqing were willing to provide bystander CPR, which was higher than the implementation willingness of the general public in China (21.2 %) [ 54 ], but lower than that of Chinese healthcare workers(73.9 %) [ 55 ]. Civil servants have a strong sense of volunteerism and are dedicated to supporting different levels of volunteering [ 56 ], and their first aid literacy is higher than that of the general public [ 57 ], which makes them more inclined to perform bystander CPR. Nonetheless, compared to healthcare workers, their willingness to perform CPR was lower, possibly due to a lack of confidence in the CPR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that 50.1 % of civil servants in Chongqing were willing to provide bystander CPR, which was higher than the implementation willingness of the general public in China (21.2 %) [ 54 ], but lower than that of Chinese healthcare workers(73.9 %) [ 55 ]. Civil servants have a strong sense of volunteerism and are dedicated to supporting different levels of volunteering [ 56 ], and their first aid literacy is higher than that of the general public [ 57 ], which makes them more inclined to perform bystander CPR. Nonetheless, compared to healthcare workers, their willingness to perform CPR was lower, possibly due to a lack of confidence in the CPR technique.…”
Section: Discussionmentioning
confidence: 99%
“…There are three reasons for the selection of the organization. First, community social organizations are an important component of social organizations, and volunteer management in social organizations is essential [21]. Second, in the Chinese context, the Ministry of Civil Affairs requires community collaboration, and social organizations, social workers, and community volunteers gather to build communities jointly.…”
Section: Methodsmentioning
confidence: 99%
“…Since the end of 2019, COVID-19 has imposed an unprecedented challenge on governments' role in ensuring basic health and economic conditions, but also food security, for their populations. In response to this challenge, many governments have relied more on voluntary and community organizations (VCOs) and citizen volunteers to deliver and co-produce basic social services (Miao et al, 2021;Pevnaya et al, 2020;Steen and Brandsen, 2020). VCOs refer to various types of non-governmental and non-market organizations, including membership-based non-governmental organizations, religious organizations, neighbourhood community organizations, and informal "pop-up" initiatives.…”
Section: Community Food Securitymentioning
confidence: 99%